INTERMETALLIC NICKEL ALUMINIDES BEING AN ALTERNATIVE FOR AUTOMOTIVE BODY APPLICATIONS - T. Joseph, Sahaya Anand (Lambert Academic Publisher (LAP), 2011)
Investigation on Intermetallic Nickel Aluminides was carried to determine the suitability of this material to replace the existing automotive body. The purpose is to produce vehicles which are lighter, more fuel efficient and cause less pollution. One key technical design strategy for improving vehicles efficiency is the light weighting. Attractive properties of Ni-Al intermetallic including low density (~ 6g/cm3) resulting lightweight, high oxidation and corrosion resistance, combined with their ability to retain strength and stiffness at elevated temperatures lead to its selection as a candidate of alternative material. The prime focus was to obtain the mechanical properties such as tensile and hardness which was tested using Universal testing machine (UTM) and Vickers Microhardness Tester. X-Ray Diffraction (XRD) was used to determine the crystal structure and lattice constant of the designed alloy. Microstructure analysis of the alloys was examined using optical microscopy and Scanning Electron Microscopy (SEM). Knowledge on microstructure gives interrelationship on mechanical and other properties of the designed alloy. SEM equipped with Energy Dispersive X-ray (EDX) used to do compositional analysis. Heat treatment (annealing) and Tafel extrapolation tests were carried out to determine thermal and corrosion properties of the alloy respectively. The properties obtain was compared with current or existing material which are high strength steel (HSS) and aluminum (luxury cars). In can be eloquent that intermetallic nickel aluminides enfold most of the basic quality for a material to be suggested or recommended as alternative material for body in white application.